Elaboração e avaliação de uma Programação de Ensino de Coesão Referencial - Mijas, Paulo Henrique Ubirajara (2019)
A text, whether written or oral, is not a mere juxtaposition of words and phrases. To guarantee meaning to textual production, it is necessary to use cohesive elements that guarantee their understanding, and Reference is an important resource related to Semantics. This is a topic that is taught in High School. A way to teach is through teaching program based on the principles of Behavior Analysis. The present work aims to elaborate and evaluate a Computer-assisted Program for Teaching Text Cohesion, directed to High School students. The teaching procedure was applied in six participants from ETIM (Ensino Técnico Integrado ao Médio) – a vocational program integrated to High School curriculum, at Etec (Escola Técnica Estadual) – public Technical School. The participants developed the activities in the computer, accessing them in a website specifically created for the research. The proposed design consisted of Pre-Test, Teaching and Post-Test. For the identification of the repertoire on Reference. Before teaching, an evaluation instrument composed by Textual Re-elaboration and Computer-assisted Assessment of items on cohesion was used. The content was taught in 16 steps, focusing on the following topics: Nominal Substitution, Verb Replacement, Ellipsis and Repetition, Reiteration, Synonym for Reiteration, Hypernym and Hyponym Reiteration, and Nominal Phrases for Reiteration. After teaching, the student's repertoire was again evaluated, and the items included in the assessment instrument used in the Pre-Test were reapplied. The results were positive; after teaching, in the Textual Re-elaboration, it was identified an increase in the number of cohesive terms used and, in the Computer-assisted Assessment, increase in the percentage of correct answers. The data showed that the participants improved their performances after the accomplishment of the teaching procedure, evidencing that the proposed program was efficient in cohesive elements of reference teaching and learning process